5
$\begingroup$

I'm having a little trouble with the following problem:

Calculate $F'(x)$:

$F(x)=\int_{1}^{x^{2}}(t-\sin^{2}t) dt$

It says we have to use substitution but I don't see why the answer can't just be:

$x-\sin^{2}x$

$\endgroup$
1
  • $\begingroup$ You can apply the following rule (Leibnitz): If $I(t)=J(u,v,t)=\displaystyle\int_{u(t)}^{v(t)}f\left( x,t\right) dx,$ then, under suitable conditions, we have $I^{\prime }(t)=\displaystyle\int_{u\left( t\right) }^{v\left( t\right) }\dfrac{\partial f\left( x,t\right) }{\partial t}dx+f\left( v\left( t\right) ,t\right) v^{\prime}\left( t\right) -f\left( u\left( t\right) ,t\right) u^{\prime}\left( t\right) .$ $\endgroup$ – Américo Tavares Oct 5 '10 at 23:12
19
$\begingroup$

If you had $G(x)=\int_{1}^{x}(t-\sin^{2}t) dt$ (note that it's just $x$ at the upper limit of the integral), then $G'(x)=x-\sin^2x$. But, you have $F(x)=\int_{1}^{x^{2}}(t-\sin^{2}t) dt=G(x^2)$, so $F'(x)=G'(x^2)\cdot2x=(x^2-\sin^2x^2)2x$ (using the chain rule).

$\endgroup$
1
  • $\begingroup$ I get it now. Thanks! $\endgroup$ – G.P. Burdell Oct 5 '10 at 22:53
4
$\begingroup$

You could apply the following more general rule (Leibniz rule and chain rule) -- although Isaac's answer is more straightforward for this derivative: If [edited in response to a Didier Piau's comment to this answer of mine]

$$I(x)=J(u(x),v(x),x),\quad \text{with}\ J(a,b,x)=\int_a^bf(t,x)dt,$$

then, under suitable conditions, we have

$$I^{\prime }(x)=\displaystyle\int_{u(x)}^{v(x)}\dfrac{\partial f(t,x)}{\partial x}dt+f(v(x),x)v^{\prime }(x)-f(u(x),x)u^{\prime }(x).$$

In this case:

$$F(x)=I(x)=\displaystyle\int_{1}^{x^{2}}(t-\sin ^{2}t)dt,$$

and

$$u(x)=1,\quad v(x)=x^{2},\quad f(t,x)=(t-\sin ^{2}t),$$

$$\dfrac{\partial f(t,x)}{\partial x}=0,\quad v^{\prime }(x)=2x,\quad u^{\prime }(x)=0.$$

Therefore

$$F^{\prime }(x)=I^{\prime }(x)=(x^{2}-\sin ^{2}x^{2})2x=2x^{3}-2x\sin ^{2}x^{2}.$$


The conditions are: $u(x),v(x)$ are differentiable functions, $f(t,x)$ is a continuous function and $\partial f/\partial x$ exists and is continuous.

$\endgroup$
1
$\begingroup$

Because the upper limit of the integral is x^2, not x.

$\endgroup$
0
$\begingroup$

Well according to me the answer is $$F'(x) = \frac{d}{dx}(x^{2}) \cdot [x^{2}-\sin^{2}(x^{2})] - \frac{d}{dx}(1) \times \text{something} = 2x \cdot \Bigl[x^{2} -\sin^{2}(x^{2})\Bigr] - 0$$ would be the answer.

$\endgroup$
0
$\begingroup$

$\displaystyle{% {{\rm d} \over {\rm d}x} = 2x\,{{\rm d} \over {\rm d}\left(x^{2}\right)} }$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.